Sex difference in the associations among risk factors with hepatitis B and C infections in a large Taiwanese population study - Wang, Angela Chiunhsien; Geng, Jiun-Hung; Wang, Chih-Wen; Wu, Da-Wei; Chen, Szu-Chia (Frontiers in Public Health, 2022)
Background The prevalence rates of hepatitis B and C virus (HBV/HCV) infection are high in Taiwan, and both are common causes of chronic liver disease and its related complications. Therefore, the early detection of factors associated with HBV/HCV infection is important. The aim of this study was to explore these factors in a large cohort of Taiwanese participants in the Taiwan Biobank, and also to identify sex differences in these risk factors. Methods It was an observational cohort study. The study enrolled 121,421 participants, and divided into four groups according to the presence or absence of HBV or HCV infection. Associations between risk factors with HBV or HCV infection were examined using multivariate logistic regression analysis. Results The mean age of the 121,421 enrolled participants (43,636 men and 77,785 women) was 49.9 ± 11.0 years. The participants were stratified into four groups according to those with (n = 13,804; 11.4%) and without HBV infection (n = 107,617; 88.6%), and those with (n = 2,750; 2.3%) and without HCV infection (n = 118,671; 97.7%). Multivariable analysis revealed that male sex [vs. female sex; odds ratio [OR] = 1.346; 95% confidence interval (CI) = 1.282–1.414; p < 0.001] was significantly associated with HBV infection, whereas female sex (vs. male sex; OR = 0.642; 95% CI = 0.575–0.716; p < 0.001) was significantly associated with HCV infection. Furthermore, there were significant interactions between sex and age (p < 0.001), body mass index (p < 0.001), total cholesterol (p = 0.002), aspartate aminotransferase (p = 0.024), and estimated glomerular filtration rate (p = 0.012) on HBV infection. There were also significant interactions between sex and age (p < 0.001), hypertension (p = 0.010), fasting glucose (p = 0.031), and uric acid (p = 0.001) on HCV infection. Conclusion In conclusion, sex differences were found among the risk factors for HBV and HCV infections in a large cohort of Taiwanese volunteers. When dealing with hepatitis B and hepatitis C, the physicians may need to pay attention to the differences between men and women to do different treatments.